Subversion in Visual and Verbal Paratexts. A Case Study of the Translation of a Contemporary Chinese Artist’s Biography - Wang, Yandi (TTR)

(untitled) (Association canadienne de traductologie, 2022)
Translation has long been integral to the circulation of art between the East and West (Whyte and Heide, 2011, p. 47). Classical Chinese art was first introduced to the West when a history of classical Chinese painting was translated into English (ibid., pp. 46-47). As indicated by the plethora of books and articles published on the subject, there is now widespread interest in contemporary Chinese art, which has achieved international acclaim since the 1990s. This paper draws on existing scholarship in translation studies and political science to analyze four types of paratext (title, cover design, epigraphs, and translator’s preface) in a biography of contemporary Chinese artist Zhang Xiaogang. Based on a comparative visual and verbal paratextual analysis, the paper examines the re-construction of the original title and cover design for the English translation of Zhang’s biography. In this “paratranslation” (Pellatt, 2013a), the translator subverts what Valerie Pellatt calls an “Occidentalist approach” in two ways: first, by privileging the source culture—China’s soft power—over the Western target readership and, second, by explicitly but subtly using rhetorical and narrative devices to convey his own social-political stance. The translated paratexts thus perform multiple functions. They promote the state’s soft power by constructing an image of an underground artist whose work, by resisting autocracy, was once suppressed by the state but is now acclaimed both nationally and internationally. Simultaneously, the translation provides a space for the translator’s voice. This study reveals the importance of translation to scholarship on contemporary Chinese art, which here goes beyond translation itself by giving the translator a voice to advocate for social awareness.